Analysis of supply chain sustainability with supply chain complexity, inter-relationship study using delphi and interpretive structural modeling for Indian mining and earthmoving machinery industry. (October 2020) - Chand, Pushpendu; Thakkar, Jitesh J.; Ghosh, Kunal Kanti
Abstract: The context of the sustainable supply chain (SSC) is progressively getting attention among supply chain (SC) managers due to its competitive advantage in firms' performance. Increasing supply chain complexity (SCC) is argued as one of the biggest risks in achieving the organisational goal with an adverse impact on operational efficiency, cost, profitability, on-time delivery, and customer satisfaction. Though drivers of SSC and SCC have seemingly demonstrated mutual relationship in a practical scenario, supply chain managers tend to address respective drivers independently for managing and controlling. Limited availability of literature investigating interactions among drivers of SSC and SCC with its overall impact on the supply chain motivates deeper research. To address the gap, current research aims to study the mutual relationship between SSC and SCC drivers. To achieve this, a combination of sequential exploratory two-phased research methodology is adopted. The Delphi technique is initially applied to identify the critical SSC and SCC drivers followed by using interpretive structural modeling (ISM) to decipher the mutual relationship among the SSC and SCC drivers. The interactions between SSC and SCC drivers explored in this work will provide supply chain managers a framework for informed decision making. The driving and dependence power of drivers can guide SC practitioners to prioritize and focus on key drivers with a high impact on the overall outcome. The organization can also be benefitted by managing SSC and SCC drivers in synergy against the silo approach. The research finding suggests that market uncertainty, institutional regulations, strategic supplier collaboration, customer pressure, and new technologies are key five drivers in decision-making. Highlights: Sustainable supply chain (SSC) and supply chain complexity (SCC) are important for firm's business performance. Inter-relationship study conducted among drivers of SSC and SCC combining Delphi and Interpretive Structural Modeling. Results suggest significant interaction among SSC and SCC drivers. Research outcome builds theoretical framework for combined decision-making in addressing SSC and SCC. Knowing the interrelationship among SSC and SCC drivers will empower supply chain managers.